2014
DOI: 10.1016/j.jmps.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the entropic force between fluctuating biological membranes

Abstract: The complex interplay between the various attractive and repulsive forces that mediate between biological membranes governs an astounding array of biological functions: cell adhesion, membrane fusion, self-assembly, binding-unbinding transition among others. In this work, the entropic repulsive force between membranes-which originates due to thermally excited fluctuations-is critically reexamined both analytically and through systematic Monte Carlo simulations. A recent work by Freund [1] has questioned the va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
2
23
1
Order By: Relevance
“…In recent studies Helfrich’s assumptions have been revisited and the force has been shown to exhibit a more complex behavior. For extremely small separations, it scales as 1/Δ h , for intermediate distances it follows Helfrich’s predictions and for larger separations, it shows an exponential decay (Freund, 2013)(Sharma, 2013)(Wennerström, Olsson, & Israelachvili, 2013)(Hanlumyuang, Liu, & Sharma, 2014). It would be important to understand how the fusion proteins overcome this force to gain insight into pore creation.…”
Section: A Physical View Of Nuclear Envelope Architecturesupporting
confidence: 60%
“…In recent studies Helfrich’s assumptions have been revisited and the force has been shown to exhibit a more complex behavior. For extremely small separations, it scales as 1/Δ h , for intermediate distances it follows Helfrich’s predictions and for larger separations, it shows an exponential decay (Freund, 2013)(Sharma, 2013)(Wennerström, Olsson, & Israelachvili, 2013)(Hanlumyuang, Liu, & Sharma, 2014). It would be important to understand how the fusion proteins overcome this force to gain insight into pore creation.…”
Section: A Physical View Of Nuclear Envelope Architecturesupporting
confidence: 60%
“…Starting with the pioneering work of Helfrich (1978), this repulsive steric interaction has been studied using the classical model of a membrane fluctuating between two rigid plates (Janke and Kleinert, 1987;Bachmann et al, 2001;Freund, 2012Freund, , 2013Hanlumyuang et al, 2014). In contrast to fluid membranes, the twin boundaries are separated by a crystalline matrix which also undergoes deformation to accommodate the fluctuations of the neighboring interfaces.…”
Section: Entropic Interaction Between Fluctuating Twin Boundariesmentioning
confidence: 99%
“…Studies based on thermal fluctuations have also shown that membranes exert a repulsive entropic pressure on each other, due to steric effects, that depends on the inter-membrane distance (Helfrich, 1978;Janke and Kleinert, 1987;Bachmann et al, 2001;Freund, 2012Freund, , 2013Hanlumyuang et al, 2014). Unlike the extensive work on the steric interaction of membranes, the effect of the presence of multiple GBs on their thermal fluctuations has not been addressed before.…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold in turn affects the hydrodynamic damping of the membrane reflected in changes of the time dependent correlation function and the associated power spectrum, the so-called power spectral density (PSD) [15,[22][23][24]. Moreover, in the cellular environment, active processes couple with the membrane fluctuations [23][24][25][26][27][28][29][30][31][32][33], resulting in the violation of the fluctuationdissipation theorem in the activated state of the cell [34][35][36].…”
Section: Introductionmentioning
confidence: 99%